2007
DOI: 10.1080/14786410701394142
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of the essential oils ofSideritis scardicaGriseb. andSideritis raeseriBoiss and Heldr. from Bulgaria and Macedonia

Abstract: The essential oils of two species of Sideritis growing spontaneously in Bulgaria and Macedonia are reported, Sideritis scardica and Sideritis raeseri. The oils of S. scardica from different locations differed significantly: in the Macedonian sample alpha-cadinol (20%) predominated, while in the oil of Bulgarian samples the main components were diterpenic compounds and octadecenol (over 20%). This is the first report of ditrpenoids in essential oil of S. scardica. The oil of S. raeseri demonstrated a distinct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 13 publications
4
32
2
2
Order By: Relevance
“…The obtained results were compared with those of samples of Bulgarian origin published previously [6], and a great difference in the chemical composition of the essential oils was observed. Thus, the oil of Population SC1, originating from Pirin Mt, was rich in monoterpene hydrocarbons (37.3%), while this type of compounds was detected at only 2.7% in the sample described by Kostadinova et al [6].…”
Section: Fig 2 Rare Essential-oil Components Identified In Sideritimentioning
confidence: 86%
See 2 more Smart Citations
“…The obtained results were compared with those of samples of Bulgarian origin published previously [6], and a great difference in the chemical composition of the essential oils was observed. Thus, the oil of Population SC1, originating from Pirin Mt, was rich in monoterpene hydrocarbons (37.3%), while this type of compounds was detected at only 2.7% in the sample described by Kostadinova et al [6].…”
Section: Fig 2 Rare Essential-oil Components Identified In Sideritimentioning
confidence: 86%
“…In contrast, Macedonian and Bulgarian S. scardica essential oils [6] were reported to be poor in monoterpenes ( < 7%). a-Cadinol (20.0%), a sesquiterpene alcohol, was the most abundant compound in the Macedonian sample, whereas in the oils of Bulgarian origin, the main components were diterpenoids ( > 21%) and octadecenol ( > 20%) [6]. Sesquiterpenoids as b-caryophyllene (18.8%) and nerolidol (12.1%) dominated in another Bulgarian sample [7].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…in Bulgaria [ 4 ]. According to the recently reported data [ 5 ], in another Macedonian S. scardica taxon the most abundant compound was hexadecanoic acid (12.9%).…”
mentioning
confidence: 99%
“…The presence of α-bisabolol, α-cadinene, isopropyl miristate, octadecenol differentiated the wild taxa from the cultivar. The method of preparation (by Clevenger [ 4 ] or Likens-Nickerson [in this study]) of the analyzed samples could result in some qualitative differences but the observed significant deviation in oil composition is probably due to the cultivation process.…”
mentioning
confidence: 99%